International Expert Consensus on Sutureless and Rapid Deployment Valves in Aortic Valve Replacement Using Minimally Invasive Approaches. Issue 3 (May 2016) - Glauber, Mattia; Moten, Simon C.; Quaini, Eugenio; Solinas, Marco; Folliguet, Thierry A.; Meuris, Bart; Miceli, Antonio; Oberwalder, Peter J.; Rambaldini, Manfredo; Teoh, Kevin H. T.; Bhatnagar, Gopal; Borger, Michael A.; et al.
Objective: To define the benefit of sutureless and rapid deployment valves in current minimally invasive approaches in isolated aortic valve replacement. Methods: A panel of 28 international experts with expertise in both minimally invasive aortic valve replacement and rapid deployment valves was constituted. After thorough literature review, the experts rated evidence-based recommendations in a modified Delphi approach. Results: No guideline could be retrieved. Thirty-three clinical trials and 9 systematic reviews could be identified for detailed text analysis to obtain a total of 24 recommendations. After rating by the experts 12, final recommendations were identified: preoperative computed to-mographic scan as well as intraoperative transesophageal echocardiography are highly recommended. Suitable annular sizes are 19 to 27 mm. There is a contraindication for bicuspid valves only for type 0 and for annular abscess or destruction due to infective endocarditis. The use of sutureless and rapid deployment valves reduces extracorporeal circulation and aortic cross-clamp time and leads to less early complications as prolonged ventilation, blood transfusion, atrial fibrillation, pleural effusions, paravalvular leakages and aortic regurgitation, and renal replacement therapy, respectively. These clinical outcomes result in reduced intensive care unit and hospital stay and reduced costs. The use of sutureless and rapid deployment valves will lead to a higher adoption rate of minimally invasive approaches in aortic valve replacement. Respect should be taken to a necessary short learning curve for both sutureless and minimally invasive programs. Conclusions: Sutureless and rapid deployment aortic valve replacement together with minimally invasive approaches offers an attractive option in aortic valve placement for patients requiring biological valve replacement.